Effects of Maternally Transferred Egg Selenium on Embryo‐Larval Survival, Growth, and Development in Arctic Grayling (Thymallus arcticus). (15th December 2020) - Brix, Kevin V.; Baker, Josh; Morris, William; Ferry, Kathleen; Pettem, Connor; Elphick, James; Tear, Lucinda M.; Napier, Robert; Adzic, Marko; DeForest, David K.
Abstract: Selenium (Se) toxicity to fish is primarily manifested via maternal transfer to the eggs, which may result in adverse effects on larval survival and development. The present study assessed the effects of egg Se concentrations derived via maternal transfer on early life–stage development, survival, and growth of Arctic grayling ( Thymallus arcticus ), a salmonid species not previously assessed for Se sensitivity. Fish gametes were collected from 4 streams in Alaska known to exhibit a range of egg Se concentrations. Eggs were fertilized and reared in the laboratory from hatch through post‐swim‐up. Larvae were assessed for survival, length, and weight, as well as deformities (skeletal, craniofacial, fin‐fold) and edema based on a graduated severity index. Eggs from a total of 47 females were collected, with egg Se concentrations ranging from 3.3 to 33.9 mg kg −1 dry weight. No relationships were observed between larval endpoints evaluated and parent females' egg, muscle, or whole‐body Se concentrations. Therefore, Se 10% effective concentrations (EC10s) were defined as the maximum measured Se concentrations: >33.9, >17.6, and >19.7 mg kg −1 dry weight for eggs, muscle, and whole‐body tissue, respectively. Collectively, these data indicate that Arctic grayling are relatively insensitive to maternally transferred Se compared to other fish species. Environ Toxicol Chem 2021;40:380–389. © 2020 SETAC